Development of Photosensitive Natural Rubber as a Mechanical Modifier for Ultraviolet-Curable Resin Applied in Digital Light Processing-Based Three-Dimensional Printing Technology - Wasan Tessanan (2022)
Natural rubber (NR), a natural product from the Hevea brasiliensis tree, has been developed as a photosensitive mechanical modifier utilized in lithography-based three-dimensional (3D) printing technology. Here, we transformed NR to photosensitive NR (PNR) by incorporating acrylate groups via chemical modifications. The acrylated NR was blended with a commercial resin (CR) at various rubber contents (0 to 3 wt %) by a simple mixing approach. The blended resin was solidified to pattern the desired specimen using a digital light processing-based 3D printer. The effect of PNR contents on mechanical properties and thermal performance of the printed specimen compared to the neat CR was studied in this work. A printed sample containing 1.5 wt % PNR can increase the elongation ability and impact strength by approximately 59 and 116%, respectively, compared to the neat CR. The microstructure of the printed objects shows a heterogeneous surface consisting of dispersed rubber droplets and a continuous CR matrix. Two glass transition temperatures belonging to the rubber phase and the resin matrix can be observed. The thermal decomposition of the printed part decreased slightly with the elevation in the rubber content. Consequently, the synthesized photosensitive natural rubber could be used as a toughness modifier employed in ultraviolet-curable resin for the light-based 3D printing technology.